FcγRII (CD32) modulates antibody clearance in NOD SCID mice leading to impaired antibody-mediated tumor cell deletion - Robert J Oldham; C Ian Mockridge; Sonya James; Patrick J Duriez; H T Claude Chan; Kerry L Cox; Vicentiu A Pitic; Mark S Cragg (Journal for ImmunoTherapy of Cancer)
Background Immune compromised mice are increasingly used for the preclinical development of monoclonal antibodies (mAb). Most common are non-obese diabetic (NOD) severe combined immunodeficient (SCID) and their derivatives such as NOD SCID interleukin-2 γ-/- (NSG), which are attractive hosts for patient-derived xenografts. Despite their widespread use, the relative biological performance of mAb in these strains has not been extensively studied.Methods Clinically relevant mAb of various isotypes were administered to tumor and non-tumor-bearing SCID and NOD SCID mice and the mAb clearance monitored by ELISA. Expression analysis of surface proteins in both strains was carried out by flow cytometry and immunofluorescence microscopy. Further analysis was performed in vitro by surface plasmon resonance to assess mAb affinity for Fcγ receptors (FcγR) at pH 6 and pH 7.4. NOD SCID mice genetically deficient in different FcγR were used to delineate their involvement.Results Here, we show that strains on the NOD SCID background have significantly faster antibody clearance than other strains leading to reduced antitumor efficacy of clinically relevant mAb. This rapid clearance is dependent on antibody isotype, the presence of Fc glycosylation (at N297) and expression of FcγRII. Comparable effects were not seen in the parental NOD or SCID strains, demonstrating the presence of a compound defect requiring both genotypes. The absence of endogenous IgG was the key parameter transferred from the SCID as reconstituting NOD SCID or NSG mice with exogenous IgG overcame the rapid clearance and recovered antitumor efficacy. In contrast, the NOD strain was associated with reduced expression of the neonatal Fc Receptor (FcRn). We propose a novel mechanism for the rapid clearance of certain mAb isotypes in NOD SCID mouse strains, based on their interaction with FcγRII in the context of reduced FcRn.Conclusions This study highlights the importance of understanding the limitation of the mouse strain being used for preclinical evaluation, and demonstrates that NOD SCID strains of mice should be reconstituted with IgG prior to studies of mAb efficacy.